(untitled) (Revista Brasileira Multidisciplinar, 2015)
This paper discusses the costs of quality in the prevention of external faults in product warranty. A case study was conducted in a commercial refrigeration company by projects that were used as tools in the quality analysis process, the PDCA cycle, the cause and effect diagram and the Pareto chart. It was found that the management of quality costs in the prevention of external faults can support companies with relevant information for decision making and the prevention of failures and noncompliance. The study also contributes to the discussion on the definition of a structure of quality costs management in the analyzed company.